Composite current collector, composite pole piece, lithium battery and preparation method

By introducing a modified layer into the composite fluid, cross-linking polymerization reaction is carried out using cross-linking agent, modifier and initiator, the problem of low adhesion of metal layer in the composite fluid is solved, and the battery performance and substrate are improved Mechanical properties.

CN119447311APending Publication Date: 2025-02-14ADVANCED MATERIALS TECH (BEIJING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410443318.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-07
Filing Date
2024-04-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing composite fluids, the adhesion between the metal layer and the substrate is low, which easily leads to the metal layer falling off, affects the energy density of the battery, and the mechanical properties of the substrate are degraded, causing battery safety performance problems.

Method used

Using a composite fluid design including a polymer layer and a conductive layer, the conductive layer is located on one side of the polymer layer, the polymer layer comprises a substrate and a modification layer, and the modification layer is passed by a crosslinker, a modifier and an initiator. Crosslinking polymerization is obtained for enhancing the bonding force between the substrate and the conductive layer and the tensile resistance of the substrate.

Benefits of technology

The bonding force between the substrate and the conductive layer is improved, the conductive layer is prevented from falling off, the battery performance is enhanced, the mechanical properties and thermal stability of the substrate are improved, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447311A_ABST
    Figure CN119447311A_ABST
Patent Text Reader

Abstract

The invention provides a composite current collector which comprises a polymer layer and a conductive layer, the conductive layer is located on at least one side of the polymer layer, and the conductive layer comprises a conductive material layer; the polymer layer comprises a base material and a modified layer, the modified layer is located on at least one surface of the base material, the modified layer is located between the conductive layer and the base material, and the modified layer comprises a cross-linked polymer and is at least obtained through a cross-linking polymerization reaction of a modifier, a cross-linking agent and an initiator; the cross-linking agent is used for enhancing the binding force between the conductive layer and the base material, and the modifier is used for enhancing the tensile property of the base material. The invention also provides a preparation method of the composite current collector, a composite pole piece, a lithium battery, a preparation method of the composite pole piece and a preparation method of the lithium battery. According to the composite current collector disclosed by the invention, the binding force between the base material and the conductive layer and the mechanical property of the composite current collector can be improved. And the conductive layer in the composite current collector disclosed by the invention is thin in thickness and light in weight, so that the energy density of the lithium battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This disclosure claims priority to Chinese Patent Application No. 202310986880.3 filed in China on August 7, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0004] The present disclosure relates to the field of batteries, and in particular to a composite current collector, a composite pole piece, a lithium battery and a preparation method thereof. Background Art

[0005] The current collector is one of the important components of lithium-ion batteries. Its function is to carry active materials, collect and conduct electrons. An ideal lithium-ion battery current collector should meet the following characteristics: high electrical conductivity, good chemical and electrochemical stability, high mechanical strength, good compatibility and binding force with electrode active materials, low cost and easy availability, and light weight. Traditional current collectors generally use aluminum foil as the positive electrode current collector and copper foil as the negative electrode current collector. However, copper foil and aluminum foil are difficult to meet people's increasingly high performance requirements for lithium-ion battery current collectors. In order to improve the performance of current collectors, people have developed composite current collectors. Compared with traditional metal foils, composite current collectors have the advantages of high conductivity, low cost, and light weight.

[0006] However, the existing composite current collectors still face the following problems: the adhesion between the metal layer and the substrate of the composite current collector is low, which easily causes the risk of the metal layer peeling off or falling off from the substrate, thereby affecting the energy density of the battery; the surface of the substrate is easily bombarded by metal particles in the magnetron and evaporation processes, which may cause the macromolecules in the polymer substrate to partially break and degrade, resulting in a significant decrease in the mechanical properties of the polymer film, causing the risk of band breakage and affecting the battery safety performance.

[0007] Therefore, it is of great significance to propose a composite current collector, a composite pole piece, a lithium battery and a preparation method to solve or at least alleviate at least one of the above technical problems. Summary of the invention

[0008] In view of the above technical problems, the present disclosure provides a composite current collector, a composite pole piece, a lithium battery and a preparation method to solve or at least alleviate at least one technical problem existing in the above composite current collector, composite pole piece and lithium battery.

[0009] According to the specific embodiments of the present disclosure, in the first aspect, the present disclosure provides a composite current collector, including a polymer layer and a conductive layer, the conductive layer is located on at least one side of the polymer layer, and the conductive layer includes a conductive material layer; the polymer layer includes a substrate and a modified layer, the modified layer is located on at least one surface of the substrate, and the modified layer is located between the conductive layer and the substrate, the modified layer includes a cross-linked polymer, and the cross-linked polymer is obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a modifier and an initiator, wherein the cross-linking agent is used to enhance the bonding force between the conductive layer and the substrate, the modifier includes at least two reactive monomers, and the modifier is used to enhance the tensile strength of the substrate.

[0010] Optionally, the modifier includes: acrylic acid or acrylic acid derivatives, and styrene or styrene derivatives.

[0011] Optionally, the cross-linking agent includes at least one of the following: dihydroxymethylurea, hydroxymethylurea, and thiourea.

[0012] Optionally, the initiator includes at least one of the following: azobisisobutyronitrile, tert-butyl perbenzoate, and ethyl ethoxypropionate.

[0013] Optionally, the mass percentage of the initiator to the cross-linking agent is 1%-5%.

[0014] Optionally, the viscosity of the cross-linked polymer is 100-300 cp, and the solid content of the cross-linked polymer is 2%-7%.

[0015] Optionally, the thickness of the polymer layer is 2.1-13 μm, wherein the thickness of the substrate is 2-12 μm, and the thickness of the modified layer is 0.1-1 μm.

[0016] Optionally, the conductive layer further includes a primer layer, which is located on a side of the conductive material layer close to the modified layer and is used to enhance the bonding force between the conductive material layer and the modified layer.

[0017] Optionally, the material of the primer layer includes a metal oxide, and / or the conductive material layer includes a metal layer.

[0018] Optionally, the conductive material layer includes aluminum or copper.

[0019] Optionally, the conductive material layer includes aluminum, and the longitudinal tensile strength MD of the composite current collector is ≥240 MPa, and the transverse tensile strength TD is ≥200 MPa; or the conductive material layer includes copper, and the longitudinal tensile strength MD of the composite current collector is ≥220 MPa, and the transverse tensile strength TD is ≥180 MPa.

[0020] Optionally, the conductive layer further includes a protective layer, and the protective layer is located on a side of the conductive material layer away from the modified layer.

[0021] Optionally, the thickness of the conductive layer is 0.12-3 μm, wherein the thickness of the primer layer is 0.01-0.1 μm, the thickness of the conductive material layer is 0.1-1.5 μm, and the thickness of the protective layer is 0.01-1.4 μm.

[0022] Optionally, the bonding force between the polymer layer and the conductive layer is greater than or equal to 3.0 N / 15 mm and less than or equal to 10 N / 15 mm.

[0023] Optionally, the substrate is a biaxially oriented polyethylene terephthalate (BOPET) film or a biaxially oriented polypropylene (BOPP) film.

[0024] According to a specific embodiment of the present disclosure, in a second aspect, the present disclosure provides a composite pole piece, comprising any composite current collector as described above.

[0025] According to a specific embodiment of the present disclosure, in a third aspect, the present disclosure provides a lithium battery, comprising any composite pole piece as described above.

[0026] According to a specific embodiment of the present disclosure, in a fourth aspect, the present disclosure provides a method for preparing a composite current collector, comprising the following steps:

[0027] Step S1, preparing a polymer layer, comprises the following steps:

[0028] Step S11, performing corona treatment on the substrate; and preparing the modified layer, specifically comprising adding a modifier, a crosslinking agent and an initiator into a solvent to obtain a modified solution, and stirring the modified solution to obtain a modified prepolymer;

[0029] Step S12, coating the modified prepolymer on at least one surface of the substrate, heating and curing the prepolymer to form a modified layer.

[0030] Step S2, providing a conductive layer on a side of the modified layer away from the substrate.

[0031] Optionally, step S2 includes:

[0032] Step S21, forming a primer layer on at least one surface of the polymer layer, specifically comprising: the primer layer comprises a metal film, and the metal film is formed on at least one surface of the polymer layer by sputtering; or the primer layer comprises a metal oxide layer, and the metal oxide layer is formed on at least one surface of the polymer layer by an in-situ reaction;

[0033] Step S22, depositing a metal layer on the surface of the base layer away from the modified layer by physical vapor deposition, thereby forming a conductive material layer on the surface of the base layer.

[0034] Optionally, after step S22, the method further includes: forming a protective layer on a surface of the conductive material layer away from the primer layer.

[0035] Optionally, the mass percentage of the modifier in the modified solution is 1%-10%.

[0036] Optionally, the modifier includes: acrylic acid or acrylic acid derivatives, and styrene or styrene derivatives, the mass percentage of acrylic acid or acrylic acid derivatives in the modified solution is 0.5%-5%; the mass percentage of styrene or styrene derivatives in the modified solution is 0.5%-5%.

[0037] Optionally, the mass percentage of the cross-linking agent in the modified solution is 1%-5%.

[0038] According to a specific embodiment of the present disclosure, in a fifth aspect, the present disclosure provides a method for preparing a composite pole piece, including any method for preparing a composite current collector as described above.

[0039] According to a specific embodiment of the present disclosure, in a sixth aspect, the present disclosure provides a method for preparing a lithium battery, including any method for manufacturing a composite pole piece as described above.

[0040] Compared with the prior art, the above scheme of the embodiment of the present disclosure has at least the following beneficial effects: the composite current collector provided by the present disclosure is provided with a modified layer between the substrate and the conductive layer, and the modified layer is a cross-linked polymer obtained by cross-linking polymerization reaction of a modifier, a cross-linking agent and an initiator, and the cross-linked polymer has good viscosity, mechanical properties and thermal stability, and can increase the bonding force between the substrate and the conductive layer, and avoid the conductive layer from falling off from the substrate during use, thereby improving the performance of the battery, and can also improve the mechanical properties and thermal stability of the substrate. Moreover, the modifier can include acrylic acid or acrylic acid derivatives, and styrene or styrene derivatives, and styrene or styrene derivatives contain benzene rings, have high stability, high rigidity, and can improve the mechanical properties of the modified layer; acrylic acid or acrylic acid derivatives increase the flexibility of the modified layer, and control the rigidity of the modified layer not to be too large, therefore, the cross-linked polymer obtained by using acrylic acid or acrylic acid derivatives and styrene or styrene derivatives in combination can make the modified layer have good mechanical properties, thereby improving the mechanical properties of the polymer current collector and increasing the battery life. In addition, the modified layer can also reduce the damage to the substrate during the sputtering of the base layer and the vacuum evaporation of the conductive material layer during the preparation of the composite current collector, further improving the mechanical properties of the composite current collector. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0042] Figure 1 Schematic diagram of the cross-sectional structure of a composite current collector in some embodiments of the present disclosure;

[0043] Figure 2 Schematic diagram of the cross-sectional structure of a composite current collector in some embodiments of the present disclosure;

[0044] Figure 3 Schematic diagram of the cross-sectional structure of a composite current collector in some embodiments of the present disclosure;

[0045] Figure 4 Schematic diagram of the cross-sectional structure of the composite current collector in some embodiments of the present disclosure.

[0046] The reference numerals in the specific implementation manner are as follows:

[0047] Composite current collector 10;

[0048] A polymer layer 1, a substrate 11 and a modified layer 12;

[0049] Conductive layer 2, primer layer 21, conductive material layer 22, protective layer 23. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure.

[0052] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such product or device. In the absence of more restrictions, the elements defined by the sentence "comprises a" do not exclude the presence of other identical elements in the product or device including the elements.

[0053] In the description of the embodiments of the present invention, the orientations or positional relationships indicated by technical terms such as "upper", "lower", and "thickness" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present invention and simplifying the description. They do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the embodiments of the present invention.

[0054] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0055] In the description of the embodiments of the present invention, the symbol “~” represents the two endpoint data before and after the “~” and all data between the two endpoints. For example, A~B represents all data greater than or equal to A and less than or equal to B.

[0056] Reference to "embodiments" in this disclosure means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the disclosure. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this disclosure may be combined with other embodiments.

[0057] See also Figure 1 The embodiment of the present disclosure provides a composite current collector 10, comprising a polymer layer 1 and a conductive layer 2, wherein the conductive layer 2 is located on at least one side of the polymer layer 1. The polymer layer 1 comprises a substrate 11 and a modified layer 12, wherein the modified layer 12 is located on at least one surface of the substrate 11, and the modified layer 12 is located between the substrate 11 and the conductive layer 2. The conductive layer 2 comprises a primer layer 21 and a conductive material layer 22, wherein the primer layer 21 is located on a side of the modified layer 12 away from the substrate 11, and the conductive material layer 22 is located on a side of the primer layer 21 away from the modified layer 12.

[0058] The conductive layer 2 is located on at least one side of the polymer layer 1. In this embodiment, the conductive layer 2 is located on two opposite sides of the polymer layer 1. Figure 2 In some other embodiments, the conductive layer 2 may also be located only on one side of the polymer layer 1. When the conductive layer 2 is located on one side of the polymer layer 1, the modified layer 12 is located on one surface of the substrate 11, and the modified layer 12 and the conductive layer 2 are located on the same side of the substrate 11; when the conductive layer 2 is located on two opposite sides of the polymer layer 1, the modified layer 12 is located on both surfaces of the substrate 11.

[0059] The material of the substrate 11 is preferably a polymer film. In some embodiments, the material of the substrate 11 includes but is not limited to polyethylene (PE), polypropylene (PP), biaxially oriented polypropylene (BOPP), polyethylene terephthalate (PET), biaxially oriented polyethylene terephthalate (BOPET), polyethylene terephthalate (PEN), poly (p-phenylene terephthalamide) (PPTA), polyimide (PI), polycarbonate (PC), polyetheretherketone (PEEK), polyoxymethylene (POM), polyphenylene sulfide (PPS), polyphenylene oxide (PPO), polyvinyl chloride (PVC), polyamide (PA) or polytetrafluoroethylene (PTFE) at least one. More preferably, when the composite current collector 10 is used as a positive current collector, the substrate 11 is a PET film or a BOPET film; when the composite current collector 10 is used as a negative current collector, the substrate 11 is a PP film or a BOPP film. BOPET film has better tensile strength, heat resistance, transparency, and is not easy to degrade compared to PET film, and BOPP film has better tensile strength, heat resistance, transparency, and is not easy to degrade compared to PP film, which is beneficial to improve the performance of the composite current collector.

[0060] The modified layer 12 includes a cross-linked polymer, which is obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a modifier and an initiator, wherein the cross-linking agent is used to enhance the bonding force between the conductive layer and the substrate, and the modifier includes at least two reactants, and the modifier is used to enhance the tensile strength of the substrate.

[0061] At least two reactive monomers in the modifier are capable of undergoing a polymerization reaction.

[0062] In some optional embodiments, the modifier includes acrylic acid or acrylic acid derivatives, and styrene or styrene derivatives. Styrene or styrene derivatives contain benzene rings, have high stability, high rigidity, and can improve the mechanical properties of the modified layer 12. Acrylic acid or acrylic acid derivatives can increase the flexibility of the modified layer 12 and control the rigidity of the modified layer 12 not to be too large. Therefore, the cross-linked polymer obtained by using acrylic acid or acrylic acid derivatives and styrene or styrene derivatives can make the modified layer 12 have suitable rigidity, improve the mechanical properties of the polymer current collector 10, and thus increase the service life of the battery. The modified layer 12 can also reduce the damage to the substrate 11 during the sputtering of the base layer 21 and the vacuum evaporation of the conductive material layer 22 during the preparation of the composite current collector 10. In addition, the cross-linked polymer of the modified layer 12 has good thermal stability, which can increase the glass transition temperature of the substrate 11, thereby improving the thermal stability of the substrate; and the cross-linked polymer of the modified layer 12 has good adhesion, which increases the bonding force between the substrate 11 and the conductive layer 2, thereby preventing the conductive layer 2 from falling off from the substrate 11 during use, thereby improving the performance of the battery.

[0063] Styrene derivatives include, but are not limited to, polystyrene, butadiene-styrene copolymers, styrene-butadiene-styrene, and the like.

[0064] Acrylic derivatives include, but are not limited to, at least one of acrylate, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, glycidyl acrylate, and glycidyl methacrylate.

[0065] The cross-linking agent allows acrylic acid or acrylic acid derivatives to undergo cross-linking polymerization with styrene or styrene derivatives to obtain a cross-linked polymer, thereby improving the adhesion of the modified layer 12 and increasing the bonding strength between the substrate 11 and the conductive layer 2. The cross-linking agent includes but is not limited to dihydroxymethylurea, dihydroxymethyl dihydroxyethylene urea, thiourea, hydroxymethyl urea, etc.

[0066] The initiator includes but is not limited to azobisisobutyronitrile, tert-butyl perbenzoate, ethyl ethoxypropionate, etc. Preferably, the mass percentage of the initiator to the mass percentage of the crosslinking agent is 1%-5%.

[0067] The viscosity of the cross-linked polymer is preferably, but not limited to, 100-300 cp, and the solid content of the cross-linked polymer is preferably, but not limited to, 2%-7%. More preferably, the solid content of the cross-linked polymer is 5%.

[0068] In this embodiment, the modifier 12 is a cross-linked polymer obtained by reacting acrylic acid, styrene, dihydroxymethylurea and azobisisobutyronitrile.

[0069] The thickness of the polymer layer 1, the substrate 11 and the modified layer 12 can be selected according to actual conditions. In some preferred embodiments, the thickness of the polymer layer 1 is 2.1 to 13 μm, wherein the thickness of the substrate 11 is 2 to 12 μm, and the thickness of the modified layer 12 is 0.1 to 1 μm. The thickness of the modified layer 12 is relatively small, and while increasing the bonding force between the polymer layer 1 and the conductive layer 2, the thermal stability of the polymer layer 1 and the mechanical properties of the polymer layer 1, the increase in the thickness and weight of the composite current collector 10 can be basically ignored, and the thickness of the polymer layer 1 is micrometer-level, thereby reducing the thickness and weight of the composite current collector 10. In this embodiment, the substrate 11 is a PET substrate, the width of the PET substrate is 380 mm, the length is 300 m, and the thickness is 6 microns. A modified layer 12 with a thickness of 300 nm is coated on the upper and lower surfaces of the PET substrate. The tensile strength of the substrate 11 is improved, wherein the longitudinal MD is increased from 297 MPa to 311 MPa, and the transverse TD is increased from 254.7 MPa to 267 MPa. The elongation at break of the substrate 11 is reduced, wherein the longitudinal MD is reduced from 93.8% to 36.1%, and the transverse TD is reduced from 110.2% to 55%.

[0070] The material of the bottom layer 21 is not limited to metal or metal oxide, the metal is preferably but not limited to nickel or NiCr alloy, and the metal oxide is preferably but not limited to AlO x , Cr2O3, NiO, etc. In some embodiments, the primer layer 21 includes a metal film, and the metal film is formed on at least one surface of the polymer layer by sputtering. In some other embodiments, the primer layer 21 includes a metal oxide layer, and the metal oxide layer is formed on at least one surface of the polymer layer 1 by in-situ reaction. The primer layer 21 is used to enhance the bonding force between the conductive material layer 22 and the modified layer 12.

[0071] It can be understood that the bottom layer 21 is an optional component, see Figure 3 In some embodiments, the conductive layer 2 does not include the primer layer 21 , and the conductive material layer 22 is directly disposed on the surface of the modified layer 12 away from the substrate 11 .

[0072] The material of the conductive material layer 22 can be a metal or a carbon conductive material. Metals include but are not limited to aluminum, copper, nickel, titanium, silver, nickel-copper alloys, aluminum-zirconium alloys, and the like. Carbon conductive materials include but are not limited to carbon nanotubes, graphene, graphite, and the like. Preferably, the conductive material layer 22 is a metal layer. In some embodiments, the composite current collector 10 is used as a positive electrode current collector, the conductive material layer 22 is metal aluminum, and the tensile strength of the composite current collector 10 is MD ≥ 240 MPa in the longitudinal direction and TD ≥ 200 MPa in the transverse direction. In other embodiments, the composite current collector 10 is used as a negative electrode current collector, the conductive material layer 22 is metal copper, and the tensile strength of the composite current collector 10 is MD ≥ 220 MPa in the longitudinal direction and TD ≥ 180 MPa in the transverse direction. Compared with existing current collectors, the tensile strength of the composite current collector 10 disclosed in the present invention is greatly improved.

[0073] See also Figure 4 In some optional embodiments, the side of the conductive material layer 22 away from the modified layer 12 further includes a protective layer 23. The protective layer 23 can prevent the conductive material layer 22 from being oxidized, corroded or damaged. In other embodiments, the composite current collector 10 is used as a positive electrode current collector, and the conductive material layer 22 is metal aluminum. The surface of the metal aluminum can form aluminum oxide by itself, and the aluminum oxide plays a role in protecting the metal aluminum. Therefore, the protective layer 23 is not provided on the side of the conductive material layer 22 away from the modified layer 12.

[0074] The thickness of the conductive layer 2, the base layer 21, the conductive material layer 22 and the protective layer 23 can be selected according to actual conditions. Preferably, the thickness of the conductive layer 2 is 0.12-3 μm, wherein the thickness of the base layer 21 is 0.01-0.1 μm, the thickness of the conductive material layer 22 is 0.1-1.5 μm, and the thickness of the protective layer 23 is 0.01-1.4 μm. The thickness of the conductive layer 2 disclosed in the present invention is much smaller than the thickness of the conventional copper foil or aluminum foil current collector, thereby reducing the weight of the current collector and the battery, and increasing the energy density of the battery.

[0075] The bonding force between the polymer layer 1 and the conductive layer 2 in the composite current collector 10 can reach 10N / 15mm. In some embodiments, the bonding force between the polymer layer 1 and the conductive layer 2 in the composite current collector 10 is greater than or equal to 3.0N / 15mm and less than or equal to 10N / 15mm, which is much greater than the bonding force between the substrate and the conductive layer in the existing composite current collector.

[0076] The present disclosure also provides a method for preparing the composite current collector 10, comprising the following steps:

[0077] Step S1, preparing a polymer layer 1, comprises the following steps:

[0078] Step S11, performing corona treatment on the substrate 11; and preparing the modified layer 12, specifically comprising adding a modifier, a crosslinking agent and an initiator into a solvent to form a modified solution, and stirring the modified solution to obtain a modified prepolymer;

[0079] Step S12, uniformly coating the modified prepolymer on at least one surface of the substrate 11, heating and curing the prepolymer to form a modified layer 12,

[0080] Step S2 , disposing a conductive layer 2 on a side of the modified layer 12 away from the substrate 11 .

[0081] In step S11, the conditions of the corona treatment are selected according to the specific material of the substrate 11. Preferably, the corona treatment is performed under 2800-3200 W. In this embodiment, the substrate 11 is a polymer film, and the polymer film is corona treated under 3000 W to increase the surface energy of the polymer film, thereby increasing the adhesion of the modified layer 12 on the surface of the polymer film.

[0082] Preferably, the modifier, the crosslinking agent and the initiator are added to the solvent and stirred under closed conditions to obtain the modified prepolymer.

[0083] The mass percentage of the modifier in the modified solution is preferably 1.0%-10%, the mass percentage of the crosslinker in the modified solution is preferably 1%-5%, and the mass percentage of the initiator in the crosslinker is preferably 1%-5%. It is understood that the amount of the modifier, crosslinker and initiator is not limited to the above mass percentages and can be adjusted according to actual conditions.

[0084] Preferably, the modifier includes acrylic acid or acrylic acid derivatives, and styrene or styrene derivatives, the mass percentage of acrylic acid or acrylic acid derivatives in the modified solution is 0.5%-5%, and the mass percentage of styrene or styrene derivatives in the modified solution is 0.5%-5%.

[0085] The solvent can be selected according to actual needs, as long as the cross-linking polymerization reaction can proceed. Preferably, the solvent is at least one of water or ethanol.

[0086] The stirring method can be selected according to actual conditions, such as ultrasonic stirring, electric stirring, mechanical stirring, etc. Preferably, ultrasonic stirring combined with mechanical stirring is used under closed conditions to uniformly mix acrylic acid or acrylic acid derivatives, styrene or styrene derivatives, crosslinking agent and initiator in the solvent.

[0087] In step S12, preferably but not limited to, a micro-gravure coater is used to uniformly coat the modified prepolymer on at least one surface of the substrate 11. The temperature of the heating reaction curing is selected according to the specific material of the modified prepolymer. Preferably, the reaction is cured at 50-100°C. The reaction curing time can be adjusted according to the actual situation, preferably but not limited to 1-10min. In some optional embodiments, the heating reaction curing can be performed by segmented gradient heating, for example, heating at 60°C for 20s, then heating at 70°C for 20s, and finally heating at 80°C for 20s.

[0088] In some optional embodiments, the modified layer 12 is formed to have a thickness of 0.1-1 μm.

[0089] In some optional embodiments, in step S2, providing the conductive layer 2 on the side of the modified layer 12 away from the substrate 11 includes: directly providing a conductive material layer 22 on the surface of the modified layer 12 away from the substrate 11. In some other optional embodiments, in step S2, providing the conductive layer 2 on the side of the modified layer 12 away from the substrate 11 includes: forming a primer layer 21 on at least one surface of the polymer layer 1, specifically, the primer layer 21 is a metal film, and the metal film is formed on at least one surface of the polymer layer 1 by sputtering; or the primer layer 21 is a metal oxide layer, and the metal oxide layer is formed on at least one surface of the polymer layer 1 by in-situ reaction; then, forming the conductive material layer 22 on the surface of the primer layer 21 away from the modified layer 12. Preferably, the conductive material layer 22 is a conductive metal layer, and the conductive material layer 22 is formed on the surface of the modified layer 12 or the primer layer 21 away from the substrate 11 by physical vapor deposition (PVD). More preferably, the conductive material layer 22 is formed on the surface of the modified layer 12 or the primer layer 21 away from the substrate 11 by evaporating metal. The evaporation method is preferably but not limited to barrier evaporation, electron gun evaporation and the like.

[0090] In some optional embodiments, step S2 further includes the step of providing a protective layer 23 on the surface of the conductive material layer 22 away from the substrate 11. In other embodiments, the composite current collector 10 is used as a positive electrode current collector, and the conductive material layer 22 is metal aluminum. Aluminum oxide can be formed on the surface of the metal aluminum, and the aluminum oxide plays a role in protecting the metal aluminum. Therefore, the protective layer 23 is not provided on the side of the conductive material layer 22 away from the modified layer 12.

[0091] According to some embodiments of the present disclosure, the present disclosure further provides a composite pole piece, comprising the composite current collector 10 provided by any of the above schemes or the composite current collector 10 obtained by the preparation method of the composite current collector provided by any of the schemes.

[0092] According to some embodiments of the present disclosure, the present disclosure further provides a lithium battery, comprising the composite pole piece provided by any of the above schemes.

[0093] According to some embodiments of the present disclosure, the present disclosure further provides a method for preparing a composite pole piece, including the method for preparing a composite current collector provided by any of the above schemes.

[0094] According to some embodiments of the present disclosure, the present disclosure also provides a method for preparing a lithium battery, including a method for manufacturing a composite pole piece provided by any of the above schemes.

[0095] The composite current collector 10 and its preparation process and test data are introduced below through specific embodiments:

[0096] Embodiment 1:

[0097] In this embodiment, the substrate 11 is a 6 μm thick PET film, and the modified layer 12 is located on the upper and lower surfaces of the PET film. The modified layer 12 includes a cross-linked polymer formed by the reaction of acrylic acid, styrene, dihydroxymethylurea, and azobisisobutyronitrile in anhydrous ethanol. The thickness of the modified layer 12 is 0.5 μm. The base layer 21 is a metal oxide AlO x The layer is formed on the upper and lower surfaces of the modified layer 12 away from the PET film by in-situ reaction, and the thickness of the primer layer 21 is 0.05 μm. The conductive material layer 22 is metal Al, and the thickness is 1.0 μm.

[0098] In this embodiment, the preparation method of the composite current collector specifically includes:

[0099] Step S1, corona treatment of the PET film at 3000W; adding 10g of acrylic acid, 10g of styrene, 1.0g of dihydroxymethylurea and 0.05g of azobisisobutyronitrile to 500ml of anhydrous ethanol to form a modified solution, performing ultrasonic and mechanical stirring under closed conditions, stirring at 30°C for 0.5h to obtain a modified prepolymer; using a micro-gravure coater to evenly coat the modified prepolymer on the upper and lower surfaces of the PET film, and then drying at 100°C for 0.2h to form a modified layer on the upper and lower surfaces of the PET film; and

[0100] Nickel is sputtered on the modified layers on the upper surface and the lower surface of the PET film to form a base layer; Al is evaporated on the base layer to obtain a composite current collector.

[0101] Embodiment 2:

[0102] The present embodiment 2 is substantially the same as the embodiment 1, and the only difference is that the substrate 11 is a PET film with a thickness of 4.5 μm, and the conductive material layer 22 is metallic copper.

[0103] Embodiment 3:

[0104] The present embodiment 3 is substantially the same as the embodiment 1, and the only difference is that the substrate 11 is a 4.5 μm thick BOPP film, and the conductive material layer 22 is metallic copper.

[0105] Comparative Example 1:

[0106] This comparative example is basically the same as Example 1, and the only difference is that the conductive layer of this comparative example is directly evaporated on the surface of the substrate, and there is no modified layer between the substrate and the conductive layer.

[0107] The bonding force between the polymer layer and the conductive layer in the composite current collector in Example 1 is 7.3 N / 15 mm. The bonding force between the polymer layer and the conductive layer in Comparative Example 1 is 2.34-5.21 N / 15 mm. This indicates that the modified layer in the composite current collector of the embodiment of the present disclosure greatly improves the bonding force between the polymer layer and the conductive layer.

[0108] Comparative Example 2:

[0109] Comparative Example 2 is substantially the same as Example 2, with the only difference being that the conductive layer of this comparative example is directly evaporated on the surface of the substrate, and there is no modified layer between the substrate and the conductive layer.

[0110] Comparative Example 3:

[0111] Comparative Example 3 is substantially the same as Example 3, with the only difference being that the conductive layer of this comparative example is directly evaporated on the surface of the substrate, and there is no modified layer between the substrate and the conductive layer.

[0112] Table 1 Comparison of composite current collector performance

[0113]

[0114] It can be seen from the performance comparison results of the composite current collector in Table 1 that the tensile strength of the composite current collector in Example 1 is 240MPa in the longitudinal direction, reaching 266MPa, and 200MPa in the transverse direction, reaching 226MPa, with strong tensile properties. The tensile strength of the composite current collector of Comparative Example 1 is 240≥MD≥200, which is 236MPa; 200≥TD≥180, which is 183MPa. It shows that the modified layer in the composite current collector disclosed in the present invention greatly improves the tensile strength of the composite current collector. The strength of the modified substrate in Example 1 is also significantly greater than the strength of the substrate in Comparative Example 1, which shows that the modified layer in the composite current collector disclosed in the present invention greatly improves the tensile strength of the composite current collector substrate. The bonding force between the modified conductive layer and the substrate in Example 1 is also significantly greater than the bonding force in Comparative Example 1, which shows that the modified layer in the composite current collector disclosed in the present invention greatly improves the bonding force between the conductive layer and the substrate.

[0115] Table 2 Comparison of composite current collector core performance

[0116]

[0117] It can be seen from the performance comparison results of the composite current collector battery cells in Table 2 that the initial discharge capacity of Examples 1-3 of the present application is greater than the initial discharge capacity of the corresponding Comparative Examples 1-3, indicating that the composite current collector battery cells formed in each embodiment of the present application have good discharge performance.

[0118] The initial charge and discharge efficiency of Examples 1-3 of the present application is greater than that of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good discharge performance.

[0119] The number of cycles of the capacity retention rate of Examples 1-3 of the present application is greater than the number of cycles of the capacity retention rate of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good discharge performance.

[0120] The energy density of Examples 1-3 of the present application is greater than the energy density of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good safety performance.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them; although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present disclosure, and they should all be included in the scope of the claims and specification of the present disclosure. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present disclosure is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A composite current collector, characterized in that: comprising a polymer layer and a conductive layer, wherein the conductive layer is located on at least one side of the polymer layer, The conductive layer comprises a conductive material layer; The polymer layer includes a substrate and a modified layer, wherein the modified layer is located on at least one surface of the substrate and between the conductive layer and the substrate, wherein the modified layer includes a cross-linked polymer, and the cross-linked polymer is obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a modifier and an initiator, wherein the cross-linking agent is used to enhance the bonding force between the conductive layer and the substrate, and the modifier includes at least two reactive monomers, and the modifier is used to enhance the tensile strength of the substrate.

2. The composite current collector according to claim 1, characterized in that: The modifier includes: acrylic acid or acrylic acid derivatives, and styrene or styrene derivatives.

3. The composite current collector according to claim 1, characterized in that: The cross-linking agent includes at least one of the following: dihydroxymethylurea, hydroxymethylurea, and thiourea.

4. The composite current collector according to claim 1, characterized in that: The initiator comprises at least one of the following: azobisisobutyronitrile, tert-butyl perbenzoate, and ethyl ethoxypropionate.

5. The composite current collector according to claim 1, characterized in that: The mass percentage of the initiator to the cross-linking agent is 1%-5%.

6. A composite pole piece, characterized in that: The composite pole piece comprises the composite current collector according to any one of claims 1 to 5.

7. A lithium battery, characterized in that: Including the composite pole piece as described in claim 6.

8. A method for preparing the composite current collector according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, preparing a polymer layer, comprises the following steps: Step S11, performing corona treatment on the substrate; and preparing the modified layer, specifically comprising adding a modifier, a crosslinking agent and an initiator into a solvent to obtain a modified solution, and stirring the modified solution to obtain a modified prepolymer; Step S12, coating the modified prepolymer on at least one surface of the substrate, heating and curing the prepolymer to form the modified layer; Step S2, providing a conductive layer on a side of the modified layer away from the substrate.

9. A method for preparing a composite pole piece, characterized in that: A method for preparing the composite current collector according to claim 8.

10. A method for preparing a lithium battery, characterized in that: Including the method for manufacturing the composite pole piece as described in claim 9.